Systemic granulomatous disease in cattle in Santa Catarina, Brazil, associated with grazing of vetch (Vicia villosa) Doença granulomatosa sistêmica em bovinos no estado de Santa Catarina associada ao pastoreio de ervilhaca peluda (Vicia villosa) - Mendes R.E. (2011)
Spontaneous intoxication in three dairy cows grazing pasture contaminated with Vicia villosa in two different farms was reported. Hyperthermia, skin alopecia and pruritus were the main clinical signs. Macroscopically, gray to white up to 5cm nodules were detected, especially in kidney and lymph nodes, which correspond to mild to severe multifocal granulomatous infiltrate. This is the first report of systemic granulomatous disease due to consumption of hairy vetch in the State of Santa Catarina, Brazil.